Twenty-Five Years Research on Micropropagation of Stevia and Curcuma sp. and Improving Secondary Metabolites using Precursor-elicitor in vitro: A Review - Delfi, Shyla Aulia; Putri, Suci Indah; Santoso, Putra; Idris, Muhammad (Jurnal Biologi Tropis, 2025)
In vitro culture technique is an effective method for plant propagation to overcome the limitations of conventional cultivation. This method is used to improve accumulation of plant secondary metabolites. The purpose of this study is to review the development of micropropagation and improving secondary metabolites in Stevia rebaudiana and Curcuma plants through the application of precursors and elicitors. The systematic literature review is used to analyse scientific articles or publications from 2000 to 2025 obtained from various online databases using relevant keywords. The results showed that Stevia was more studied when compared to Curcuma due to its high economic value, with significant impact on the study of improving accumulation of stevioside and rebaudioside production through several elicitor and precursors. In Curcuma, beside in vitro culture for mass propagation, the response to in vitro treatment of elicitor dan precursors were varied, but some precursors such as phenylalanine were shown to improve curcuminoid accumulation. In conclusion, tissue culture techniques and the use of elicitor and precursor for improving secondary metabolites accumulation have the potential impact to support mass propagation, production and sustainable optimization of plant bioactive compounds.